Evaluating the explainability of BrainGNN on prediction of ASD diagnosis - Dantas, Matheo Angelo Pereira; Carvalho, André Carlos Ponce de Leon Ferreira de (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
Due to the absence of a biological marker for Autism Spectrum Disorder (ASD), most of recent research attempts to uncover the neurological patterns of ASD using Deep Learning, and these patterns, hidden in the latent feature space of neural networks, have to be interpreted with the use of Explainable AI. However, although many of the models proposed for the problem report results of explainability, they are not evaluated with any metric, so their reliability is unknown. The objective of this paper is to propose an evaluation framework to fill this gap, and here, we focus on a detailed analysis of a well-known model from the literature, BrainGNN. We trained BrainGNN in varying hyperparameter settings that influence explainability and analyzed our findings for each case.